Effectiveness of Powered Toothbrushes Compared to Manual Toothbrushes in Reducing Plaque and Gingivitis: A Systematic Review - Solachuddin, Ayako Aziza; Solachuddin, Shafa Syahida; Zakki, Muhamad; Riyadi , Nugroho Ahmad; Suriyah, Wastuti Hidayati (YARSI Dental Journal, 2025)
Introduction: Toothbrushing is a fundamental daily practice for plaque removal. Dental plaque is a complex microbial biofilm that serves as a primary etiological factor for caries, gingivitis, and periodontitis. While manual toothbrushes (MTB) are widely used and considered effective, powered toothbrushes (PTB) are found to be a better alternative with numerous clinical trials proving their efficacy. Objective: To evaluate the effectiveness of PTB compared to MTB in reducing plaque and gingivitis based on existing literature. Methods: A systematic search was conducted to obtain clinical trials that compares plaque and gingivitis reduction with PTB and MTB usage across all age groups, using three databases - Pubmed, Scopus, and ScienceDirect. Discussion: 18 studies (69%) fully supported the hypothesis that PTB caused significantly greater reduction in plaque and gingivitis than MTB. However, seven studies (27%) found no significant differences between the two types, while one study (4%) partially supported the hypothesis, where it found PTB to be superior for plaque reduction but not for gingivitis. Overall, PTB were superior in reducing plaque and gingivitis, particularly in general populations. However, the benefits were less consistent in specific populations, such as orthodontic patients and individuals with special needs. Both oscillating-rotating and sonic PTB were comparable in their effectiveness. Conclusion: PTB are more effective than manual toothbrushes for improving plaque and gingival health in most populations. Further research is needed to address specific populations and optimise oral hygiene strategies tailored to their needs.